Juridical Analysis of Sexual Crimes Against Children (Study of Decision No.989/Pid.S/2021/PN.Bdg): Juridical Analysis of Sexual Crimes Against Children (Study of Decision No.989/Pid.S/2021/PN.Bdg) - ismirza briliana (JOSAR (Journal of Students Academic Research), 2022)
Abstract This study aims to find out what is the reason for the Bandung District Court judge in canceling the death sentence and chemical castration to the Defendant in the Case of Sexual Violence against Children, then to find out the reason the Judge only gave life imprisonment and a fine. The research method in this thesis is normative juridical which aims to examine a court decision or decision on Decision No. 989/Pid.S/2021/PN.Bdg. The results obtained are that the Bandung District Court Judge related to the Child Sexual Violence Case decided to cancel the decision on the death penalty and chemical castration in Decision Number 989/Pid.S/2021/PN.Bdg for several reasons. The cancellation occurred because the Defendant still has human rights that cannot be eliminated by the Judge, therefore the Judge imposes Compensation for the Defendant which will be given to the Victim. The cancellation was what changed the criminal sentence against the Defendant who was initially sentenced to Article 81 paragraph (1), paragraph (3), paragraph (5) jo. Article 76 D of the Republic of Indonesia Law Number 17 of 2006 concerning the Stipulation of Government Regulation in Lieu of Law No.1 of 2016 concerning the Second Amendment to Law Number 23 of 2002 concerning Child Protection to become Law Jo Article 65 paragraph (1) of the Criminal Code becomes life imprisonment and a fine of Rp. 331.527,186,- (three hundred and thirty-one million five hundred twenty-seven thousand one hundred and eighty-six rupiah).